Developing economic cooperation in modern conditions. The case of Ukraine and China - Natalya Chernenko; Leonid Solodovnyk; Harry Randhawa (CES Working Papers, 2017)
Ukraine and People's Republic of China (PRC) are cooperating in some areas like: machinery, transportation etc. China is interested in partnering with Ukraine for selling Chinese consumer goods. Ukraine is interested in selling raw materials to China. To study this possible cross-border cooperation and commercial relationship, the current paper uses the "intensity of interaction" (namely, the depth of integration) model, which is based upon the existing “gravity model”. The index for existing model has been obtained by adding a “dummy variable” in the standard "gravity model" which reflects the influence of regional nuances upon the level and direction of trade flow. The strategic partner relationship must be based on: "complementing" the economic structure of the partners, which means equality in the relationship and lack of significant disparities.
Keywords: F5; F6; 330; the gravity model; strategic partnership; scientific-technical cooperation; Ukraine - China relationship